The Case for BPA as an Obesogen: Contributors to the Controversy - Rubin, Beverly S.; Schaeberle, Cheryl M.; Soto, Ana M. (Frontiers in Endocrinology, 2019)
Since the inception of the term endocrine disruptor, the idea that the environment is an important determinant of phenotype has motivated researchers to explore the effect of low dose exposure to BPA during organogenesis. The syndrome observed was complex, affecting various endpoints such as reproduction and reproductive tissues, behavior, mammary gland development and carcinogenesis, glucose homeostasis, and obesity. This constellation of impacted endpoints suggests the possibility of complex interactions among the multiple effects of early BPA exposure. One key finding of our rodent studies was alterations of energy and amino-acid metabolism that were detected soon after birth and continued to be present at all time points examined through 6 months of age. The classical manifestations of obesity and associated elements of metabolic disease took a longer time to become apparent. Here we examine the validity of the often-mentioned lack of reproducibility of obesogenic effects of BPA, starting from the known environmental causes of variation, which are diverse and range from the theoretical like the individuation process and the non-monotonicity of the dose-response curve, to the very pragmatic like housing, feed, and time and route of exposure. We then explore environmental conditions that may hinder reproducibility and discuss the effect of confounding factors such as BPA-induced hyperactivity. In spite of all the potential sources of variation, we find that some obesogenic or metabolic effects of BPA are reproducibly observed when study conditions are analogous. We recommend that study authors describe details of their study conditions including the environment, husbandry, and feed. Finally, we show that when experimental conditions are strictly maintained, reproducibility, and stability of the obese phenotype is consistently observed.